Object-translocation induces event coding in the rat hippocampus - Ya-Li Duan; Shu-Yi Hu; Xiao-Fan Ge; Jia-Li Long; Chu Deng; Yu-Ming Sun; Cheng-Ji Li; Rong Zhang; Xing Cai; Li Lu (Communications Biology)
Abstract Episodic memory is the ability to recall personally experienced events that are situated within specific spatial contexts. Within a navigation environment, salient objects can function as landmarks, and interactions with them can be encoded as distinct episodic events. However, the nuanced integration of “where” and “what” aspects of objects during episodic memory formation remains poorly understood. In this study, we conduct a comprehensive analysis of neuronal responses along the rat CA1 proximodistal axis to manipulations of environmental cues and object features. Our results demonstrate that the proximal and distal portions of CA1 preferentially represent landmarks and events, respectively. Following object displacement, we identify an event-like population coding within CA1, distinct from the anticipated pattern of landmark representation. These findings elucidate the specific roles that objects may play in spatial navigation and memory encoding, providing novel insights into the selective processing of object-related information within the entorhinal-hippocampal network under varying conditions.